Cries from the lost island - Gear, Kathleen O'Neal (DAW book collectors, 2020)
"This standalone fantasy brings an ancient Egyptian mystery to life against a modern background, in a tale expertly crafted by a seasoned anthropologist. Set against the glory and tragedy of ancient Roman Egypt, this novel brings to bring to life the greatest love story of all time. Sixteen-year-old Hal Stevens is a budding historical scholar from a small town in Colorado. A virtual outcast at high school, he has only two friends: Roberto the Biker Witch and Cleo Mallawi. Cleo claims to be the reincarnation of Queen Cleopatra. She also believes she's being stalked by an ancient Egyptian demon, Ammut, the Devourer of the Dead. But when Hal and Roberto find Cleo murdered in the forest near her home, it appears she may have been telling the truth. Her last request sends them journeying to Egypt with famed archaeologist Dr. James Moriarity, where it quickly becomes clear that Cleo has set them on the search of a lifetime: the search for the lost graves of Marc Antony and Cleopatra. But they are not alone in their search. Cleo's murderers are watching their every move. And not all of them are human..."--